The Guardian’s departure from X: An analysis of the tone and emotions of journalistic audiences’ comments on four platforms - Santos, R. B.; Costa, B. F. (Brazilian Journalism Research, 2026)
The Guardian newspaper announced it would stop sharing its news on X (formerly Twitter). When Elon Musk bought Twitter, he reduced moderation mechanisms in the name of freedom of expression. However, these changes have accentuated the challenge for newspapers to manage audience participation. Against the backdrop of the ethical and deontological duty of media companies to dynamize and moderate participatory spaces, this study analyzes the tone and its relationship with the emotional expressions that characterized people’s reactions in comment boxes to the announcement on Facebook, Instagram, TikTok, and X (n = 41.320). LIWC-22 software was used to analyze the tone of the comments. To conduct an emotion recognition analysis, Ekman’s works were used. The news comments showed higher scores for positive tone on Instagram and negative tone on X. This study shows how emotional categories affect the tone of comments over time.